ANALISIS KONDISI KERUSAKAN JALAN PADA PERMUKAAN PERKERASAN LENTUR MENGGUNAKAN METODE PCI SERTA ALTERNATIF PENANGANANNYA (Studi Kasus : Jl. Raya Papar Kertosono, Kab Kediri STA 0+000 – 3+000) - Shafiul Oktavian; Laily Endah Fatmawati; Nurani Hartatik (LPPM Universitas Abdurrab, 2023)
Roads include land transportation facilities that are widely used for Indonesians in traveling near or far. The growth of globalization can also have an influence on the level of mobility which has an impact on vehicle users and continues to increase. This causes the volume load of vehicles to exceed the limits of the designed road class, so that the quality and age of the pavement will continue to decrease. This research was conducted to analyze the condition of road pavement damage to damage to the Jl. Raya Papar – Jl. Raya Minggir with a length of 3 km. The method used for this research is PCI (Pavement Condition Index) with the aim of finding values ​​based on the type, level and extent of damage to the method used and the selection of alternative treatments as a reference and road maintenance effort. The results of the research on the Jl. Raya Papar – Jl. Raya Minggiran STA 0+000 – 3+000 based on the PCI method obtains a total value of 47.6% Moderate (Fair) with the highest PCI value percentage of road conditions being 55% in Moderate road conditions (Fair), 25% in Bad road conditions (Poor), 8.3% on Good (Good) and Very Good (Very Good) road conditions, 3.4% on Very Bad (Very Poor) road conditions with alternative handling is periodic maintenance updates. Keywords : Road Damage, Road Conditions, PCI